2016
DOI: 10.1002/acn3.364
|View full text |Cite
|
Sign up to set email alerts
|

Staged anticonvulsant screening for chronic epilepsy

Abstract: ObjectiveCurrent anticonvulsant screening programs are based on seizures evoked in normal animals. One‐third of epileptic patients do not respond to the anticonvulsants discovered with these models. We evaluated a tiered program based on chronic epilepsy and spontaneous seizures, with compounds advancing from high‐throughput in vitro models to low‐throughput in vivo models.MethodsEpileptogenesis in organotypic hippocampal slice cultures was quantified by lactate production and lactate dehydrogenase release int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Although logical, there was a counterargument that many of the current epilepsy medications were based on drug testing in normal animals. Regardless, there is an increasing need for "high throughput" models such as zebrafish, 32 organotypic hippocampal cultures, 33 patient-derived stem cells, 34 and organoids. 35 Advances in computational models have also led to new ways to study epilepsy.…”
Section: Animal Models Of Epilepsymentioning
confidence: 99%
“…Although logical, there was a counterargument that many of the current epilepsy medications were based on drug testing in normal animals. Regardless, there is an increasing need for "high throughput" models such as zebrafish, 32 organotypic hippocampal cultures, 33 patient-derived stem cells, 34 and organoids. 35 Advances in computational models have also led to new ways to study epilepsy.…”
Section: Animal Models Of Epilepsymentioning
confidence: 99%
“…Nevertheless, the OHSC model can still give valuable information on discovering new drug targets and pathways in TBI-induced epilepsy. One good example is the high-throughput in vitro OHSC model recently developed by Staley’s group [ 32 ]. They screened over 400 compounds and found that celecoxib, a selective cyclooxygenase-2 inhibitor, was most effective at inhibiting ictal activity and ictal cell death in OHSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Organotypic hippocampal slice culture has been developed to recapitulate posttraumatic epileptogenesis in vitro. In this model, interictal‐like population spikes develop over a period of roughly 2 weeks in culture and are followed by the generation of spontaneous SLEs . Organotypic cultures must be prepared from very young animals, and the development of epileptiform activity may be sensitive to variations in culture conditions.…”
Section: General Categories Of Models and Their Benefits/limitationsmentioning
confidence: 99%
“…Caveats of using organotypic slice culture include cell death, glial proliferation, and slicing‐ and culture‐induced network reorganization. This approach is especially useful in identifying novel antiepileptogenic compounds, as cultures can be monitored and maintained for prolonged periods …”
Section: General Categories Of Models and Their Benefits/limitationsmentioning
confidence: 99%